2016
DOI: 10.1177/0020764016631364
|View full text |Cite
|
Sign up to set email alerts
|

Exploring communication of traumatic experiences from Khmer Rouge genocide survivors to their offspring: In-depth interviews with both generations

Abstract: The study discloses the complexity, pros and cons of intergenerational sharing of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…The way in which parents struggle between keeping silent and disclosing aspects of their experiences with collective violence to their children has been a key issue in studies about intergenerational legacies of genocide across the world (Braga et al, 2012; Eastmond & Selimovic, 2012; Eramian & Denov, 2018; Jordanova, 2012; Kagoyire & Richters, 2018; Kahn & Denov, 2019; Kidron, 2009; 2012; Melander et al, 2016; Münyas, 2008; Parens, 2009; Rosenthal, 2002). Many of these studies focus on the effects these choices have on the mental health and psychosocial wellbeing of the children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The way in which parents struggle between keeping silent and disclosing aspects of their experiences with collective violence to their children has been a key issue in studies about intergenerational legacies of genocide across the world (Braga et al, 2012; Eastmond & Selimovic, 2012; Eramian & Denov, 2018; Jordanova, 2012; Kagoyire & Richters, 2018; Kahn & Denov, 2019; Kidron, 2009; 2012; Melander et al, 2016; Münyas, 2008; Parens, 2009; Rosenthal, 2002). Many of these studies focus on the effects these choices have on the mental health and psychosocial wellbeing of the children.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies conducted among Khmer Rouge genocide survivors and their descendants in Cambodia come to findings different from those of Kidron (2012). Survivor parents in Cambodia do inform their offspring about their traumatic experiences with different results in terms of descendants’ wellbeing, ranging from gratitude for being born after the Khmer Rouge era and empowerment, to disbelief and feelings of anger, fear, and revenge (Melander et al, 2016; Münyas, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…While the parental understanding and attitudes towards disabilities might be influenced both by religion and current prevailing Western notions of biomedical causality, siblings may in turn be influenced by the members of the multigenerational family as grandparents share the same house or live quite close-by. A study which addressed intergenerational transmission of trauma in Cambodia reported how parents and grandparents may use their experiences, beliefs, and attitudes to discipline their children in the process shaping their belief system on health, trauma, and disabilities (Melander et al 2016).…”
mentioning
confidence: 99%